Administrative defense in the environmental sphere: an analysis based on actions in Rondônia (Research, Society and Development, 2023)
The present study proposes a reflection based on the challenges that Brazilian Environmental Law currently experiences in view of the complexities and dynamics scenario involving the exploitation of natural resources. For the present study, the research method of bibliographic analysis was used, using as references the Constitution of the Federative Republic of Brazil of 1988 and the National Environmental Policy Law. In the first part of the text, a brief history of environmental law is presented, where the basic principles of environmental law and the types of infractions are listed. Next, it discusses how the administrative process begins, and, starting from the assessment, the structure of the administrative process is presented, as well as deadlines, and ends with the forms of defense and resources, and types of sanctions that can be applied.